Judicial Jurisdiction and Choice of Law in Interstate Accident Cases: The Implications of Shaffer v. Heitner - Robert Allen Sedler (Washington University Law Quarterly, 1978)
The decision in Shaffer v. Heitner will have an important impact on the law of judicial jurisdiction.
Keywords: Jurisdiction